The gender stereotypes role in the context of family education problems - Приходько, Ганна Василівна (Pedagogy of Higher and Secondary Education, 2013)
Prihodko A. V. The gender stereotypes role in the context of family education problems. The article is devoted to the role of gender stereotypes. According to the text gender stereotypes are influences over the contents, principles and methods of the family education; determines the degree of parents’ participation in this process and there relations with boys and girls.